Zeno Cosini's Philosophy of Humor - Nikopoulos, James (Forum Italicum, 2012)
This article argues that Zeno Cosini's famous sense of humor derives from a philosophy of nihilism. Because this philosophy expresses itself as humor, as a mode of communication traditionally considered antithetical to everything associated with nihilism, the root of Zeno’s penchant for joke making oftentimes remains hidden from view. Hence, this article looks at the philosophy that underlies Zeno Cosini’s humor while aiming to assess just how ‘readable’ to others said humor renders this philosophy. This ‘readability’ is considered in light of Zeno’s relationship to three audience groups: those within the narrative who are ignorant of Zeno’s journal; Doctor S., the one character who is privy to the journal’s contents; and the readers of the journal, who know what Zeno’s doctor does but who lie outside the space of the narrative.
Keywords: humor; philosophy; nihilism